Navigating the digital frontier: platform work and its challenges in the Western Balkans - Radivojevic, Vladimir (Sociološki pregled, 2025)
The paper explores the platform economy’s development in the Western Balkans, highlighting its unique challenges and opportunities. It aims to understand the regional impact of digital transformation, focusing on barriers such as limited digital infrastructure, regulatory hurdles, and significant gender disparities in the online workforce. The research employs comparative analysis and case studies to examine these issues, identifying critical gaps in legislative protections and varying degrees of gender representation and earnings. By emphasizing the need to improve digital literacy and enhance competition, the study offers well-founded measures for advancing the digital economy in this region and underscores additional avenues for future research. The findings are particularly beneficial for policymakers, platform entrepreneurs, and other stakeholders seeking to address regional inequalities, improve digital inclusion, and foster a more equitable and resilient platform economy in the Western Balkans.